U.S. Department of Agriculture exhibition display (1926)
Two views of the U.S. Department of Agriculture's exhibition display at the Chemical Industries Exposition in New York. Highlighting the work of the Fixed Nitrogen Research Laboratory, the display includes panels on fertilizers and fixed nitrogen and soils, as well as assorted sample jars, glassware, and a photograph viewer. The Fixed Nitrogen Research Laboratory (F.N.R.L.) was established at American University in 1919 under the directorship of Arthur B. Lamb. Initially part of the War Department, the F.N.R.L. was the successor to several wartime initiatives to develop a secure domestic supply of nitrate compounds necessary for the manufacture of explosives during World War I. With a staff of about 110 individuals, including 35 to 50 chemists, the F.N.R.L. focused on the manufacture, production, and development of products of atmospheric nitrogen, including munitions and fertilizers.
Keywords: Nitrogen fertilizer industry; Exhibitions; Nitrogen--Fixation; United States. Bureau of Chemistry and Soils; United States. Department of Agriculture